Evaluation of integrated anxiety stress states and quality of life of healthcare workers during the COVID-19 process (Annals of Medical Research, 2022)
Aim: This study aimed to examine integrated anxiety and stress states and quality of life of healthcare workers during the COVID-19 process and the relationship between them.Materials and Methods: The population of this descriptive, cross-sectional, and correlational study consisted of all healthcare workers working during the COVID-19 process in Turkey. The research sample consisted of 305 healthcare workers who could be reached online between 12 June and 25 August 2020. In the study, a “Personal Information Form”, the “Integrated Anxiety-Stress Scale (IASS)”, and the “Professional Quality of Life Scale (ProQOL)” were used.Results: Of the healthcare workers, 85.2% were female, 72.5% were married, and 81.6% were nurses. 59.7% of them were assigned to COVID-19 units during the pandemic process. The mean total IASS score of the healthcare workers was 56.34±28.70 and the mean IASS index score was 26.17±8.30. The mean scores on the subscales of ProQOL were 32.64±10.17 for professional satisfaction, 15.70±9.32 for empathy fatigue, and 19.88±7.22 for burnout. A strong significant relationship was found between the integrated anxiety/stress scale and the subscales of the professional quality of life scale (p
Keywords: Anxiety-stress; COVID-19 pandemic; Healthcare workers; Professional quality of life